Quantifying Bone–relevant Activity and its Relation to Bone Strength in Girls - Farr, Joshua N. (2011)
Physical activity (PA) is critical for maximizing bone development during growth. However, there is no consensus on how well existing PA measurement tools predict bone strength. PURPOSE: Compare four methods of quantifying physical activity (PA) (pedometer, 3-day physical activity recall (3DPAR), bone-specific physical activity questionnaire (BPAQ), and past year physical activity questionnaire (PYPAQ)), in young girls and evaluate their ability to predict indices of bone strength. METHODS: 329 girls aged 8–13 years completed a pedometer assessment, the 3DPAR, the BPAQ, and a modified PYPAQ. Peripheral quantitative computed tomography (pQCT) was used to assess bone strength index (BSI) at metaphyseal (4% distal femur and tibia) sites and strength-strain index (SSI) at diaphyseal (femur = 20%, tibia = 66%) sites of the non-dominant leg. Correlations and hierarchical multiple regression were used to assess relationships among PA measures and indices of bone strength. RESULTS: After adjustment for maturity, correlations between PA measures and indices of bone strength were positive, although low (r = 0.01–0.20). Regression models that included covariates (maturity, body mass, leg length, and ethnicity) and PA variables showed that PYPAQ score was significantly (P < 0.05) associated with BSI and SSI at all sites and explained more variance in BSI and SSI than any other PA measure. Pedometer steps were significantly (P < 0.05) associated with metaphyseal femur and tibia BSI and 3DPAR score was significantly (P < 0.05) associated with metaphyseal femur BSI. BPAQ score was not significantly (P > 0.05) associated with BSI or SSI at any sites. CONCLUSION: A modified PYPAQ that accounts for the duration, frequency, and load of PA predicted indices of bone strength better than other PA measures.